PERCEPÇÕES DE AUDITORES SOBRE AS ATIVIDADES DO CONTROLE INTERNO NA ADMINISTRAÇÃO PÚBLICA DO ESTADO DO ESPÍRITO SANTO - Zucolotto, Anderson de Freitas (2022)
Objective: This research aims to analyze the perceptions of the auditors of the Secretaria de Controle e Transparência (SECONT) on the activities of internal control (CI) in the Public Administration of the Executive Branch of the state of Espírito Santo. Methodology: The study uses a qualitative method as a way of analyzing the subject-matter. Under the point of view of the research approach, a descriptive and explanatory mode was employed. As for the procedure and methodological approach to data collection, this study was survey type research, having the SECONT auditors as its object. Data collection for the empirical investigation was carried out through a questionnaire method, applied individually and online, through the Google Forms platform. Finally, the data processing took place through the analysis of the respondents’ understanding of the researched object. Results: SECONT's institutional mission is well widespread within the Organization, as the surveyed auditors state that the improvement of management is considered essential for the performance of their functions. It appears that there is an interest on the part of the researched in continuing education for acquiring knowledge, in order to improve their professional performance. On the other hand, the Agency does not encourage them to the same extent. Based on the understandings exposed by the objects of the survey, it can be perceived a certain distance between the effective exercise of auditing and what has been advocated by national and international contemporary standards, undermining democratic accountability, which is more procedural and less democratic. The institution's auditors still tend to carry out compliance audits, focusing on meeting standards and laws, which can be justified by the mimetic isomorphism that occurred in subnational entities after the creation of the Controladoria-Geral da União in 2003, considered a model of public institution of the System of Internal Control (SCI). Standardized answers from the auditors are also verified, considering that for some questions there were percentages of 70, 90 points, reaching 100% at times. Contributions: The present study contributes to the research on the CI within the public sector, and mainly to the activities developed at SECONT. Thus, it presents perceptions about the actions performed by the auditors of the Agency, serving as insights for the higher authorities of the Institution and the Government, regarding the improvements achieved in the past, as well as the need to submit to the advances of the national and international SCI.